The impact of patient-centered care on the patient experience - Alshammari, Fawaz Awdah Mohammad (International journal of health sciences, 2023)
Healthcare providers are not combining their knowledge of mental health symptoms and treatments with their patients’ individual needs and preferences. This can apply to all aspects of health services, and a number of policies increasingly support the concept of "patient-centered care." We talk about the role of organizational climate in supporting the move towards patient-centered care and look at some of the relevant research in the field. Contemporary healthcare practice emphasizes a model of care that values patient preferences and inclusion; however, this is a relatively recent development. The antecedents of this care model have deep roots. Over two decades ago, some healthcare providers recognized that patient priorities are not always aligned with clinical outcomes.